1947
DOI: 10.1084/jem.85.6.701
|View full text |Cite
|
Sign up to set email alerts
|

Factors Involved in Production of Clostridium Welchii Alpha Toxin

Abstract: Various simplified media have been described in which Clostridiura welchii grows well but produces no alpha toxin (1-3). Macfarlane and Knight (4) showed that the addition of autolyzed muscle to a medium which is satisfactory for growth enhanced the production of alpha toxin. Rogers and Knight (5) presented evidence indicating that the effect of autolyzed muscle was in part due to glucosamine. Logan, TyteU, Danielson, and Griner (6) used a pancreatic digest of beef heart as a source of "toxin factor" and fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1957
1957
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Numerous studies attribute the control or regulation of protein synthesis to a specific nutrient (1,3,17,26). C. perfringens enterotoxin production may also be regulated by nutritional factors.…”
mentioning
confidence: 99%
“…Numerous studies attribute the control or regulation of protein synthesis to a specific nutrient (1,3,17,26). C. perfringens enterotoxin production may also be regulated by nutritional factors.…”
mentioning
confidence: 99%
“…Moreover, the current feeding regimes also provide lower amounts of milk replacer compared to the previous regimes. Contact with milk protein has been observed to decrease alpha toxin production by C. perfringens , which may influence antibody production against this toxin ([ 22 ], confirmed by unpublished data in supplementary materials ). Since the provision of solid feed did not influence the antibody dynamics of C. perfringens alpha toxin and perfringolysin, differences in quantity and quality of milk replacer used in veal calves compared to beef calves might lead to different exposure to alpha toxin, possibly explaining the difference in antibody production observed in both studies.…”
Section: Resultsmentioning
confidence: 73%
“…The pTrcHisA plasmids encoding native perfringolysin (Department of Microbiology and Immunology, College of Medicine, University of Oklahoma, USA) were transformed in chemically competent E. coli TunerTM(DE3)pLysS cells (Novagen, Darmstadt, Germany). The proteins were expressed in Terrific Broth (24% Tryptone (Oxoid, Hampshire, UK), 42% Yeast extract (BD), 4% glycerol, 0.72 M Na 2 HPO 4 , 0.16 M NaH 2 PO 4 ) and the protein expression was induced with 0.5 mM isopropyl β- d -thiogalactopyranoside (IPTG, Promega, Madison, WI, USA) [ 22 ]. The E. coli cells were lysed by sonication in a lysis buffer (pH 7.4) containing 20 mM NaPO 4 , 0.5 M NaCl, 20 mM Imidazole, 1 mg/mL lysozyme (Sigma-Aldrich, St. Louis, MO, USA) supplemented with protease-inhibitor cocktail (Sigma-Aldrich, St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Gordon, Turner & iDmochowski (1954) reported that lecithin inhibited the haemolytic activity of lecithinase. Although Adams, Hendee & Pappenheimer (1947) found that lecithin stimulated lecithinase production, their experiments were performed in a complex non-synthetic medium.…”
Section: Effect Of Synthetic Lecithin On Lecithinase Productionmentioning
confidence: 99%